2015
DOI: 10.1039/c5ra03364k
|View full text |Cite
|
Sign up to set email alerts
|

Scalable synthesis of two-dimensional antimony telluride nanoplates down to a single quintuple layer

Abstract: Scalable syntheses of two-dimensional topological insulators are critical to material exploration. We demonstrate a controlled assembly of a two-dimensional V-VI group compound, Sb 2 Te 3 nanoplates (NPs), through a vapor-solid growth process. The physical thickness of Sb 2 Te 3 NPs can be rationally controlled in a wide range, from hundreds of nm down to sub-10 nm. Single-quintuple-layer Sb 2 Te 3 NPs were obtained, with a high domain density of $2.465  10 8 cm À2 over a large surface area (1 cm  1 cm) of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…S2). Such nucleation center was also observed previously during the deposition of Sb 2 Te 3 quintuples by vapor solid method 25 . The energy dispersive X ray (EDS) analysis is shown in the insets of the Fig.…”
Section: Resultssupporting
confidence: 84%
“…S2). Such nucleation center was also observed previously during the deposition of Sb 2 Te 3 quintuples by vapor solid method 25 . The energy dispersive X ray (EDS) analysis is shown in the insets of the Fig.…”
Section: Resultssupporting
confidence: 84%
“…It has been suggested in literature that this color change is due to quantumconfinement. 13 It can be observed that the color change of the material is dramatic as thickness is minimized in Fig. 1c.…”
Section: -3mentioning
confidence: 84%
“…Furthermore, Auger electron spectroscopy is utilized to verify that the changes in optical properties arise from oxidation. This investigation clarifies the origin of thickness-and chemistry-dependent 13 A 100 nm SiO 2 /Si target substrate was placed 5 cm from edge of the furnace, and source powder was placed in the furnace center. The chamber was first evacuated starting by evacuated to 15 mTorr vacuum for 30 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many new 2D nanomaterials have been prepared by CVD technology. The controllable growth of Sb 2 Te 3 nanosheets occurs on the surface of SiO 2 [ 81 ]. Bismuth oxide monocrystalline films could be prepared on amorphous substrates by aerogel-assisted CVD [ 82 ].…”
Section: Synthesis Of Xenesmentioning
confidence: 99%